THE IMPLEMENTATION OF ENVIRONMENTAL ACCOUNTING FOR WATER PRODUCTION RESIDUES (A CASE STUDY AT THE REGIONAL PUBLIC DRINKING WATER COMPANY PERUMDA MUARA TIRTA, GORONTALO CITY) - Dzulkarnain Agung Mooduto; Mahdalena; Ronald S. Badu (PT. Jurnal Center Indonesia Publisher, 2026)
The objective of this study is to examine the management of water production residues and to analyze their implementation in environmental accounting at PERUMDA Air Minum Mutiara Tirta, Gorontalo City. This study employs a qualitative method with a case study approach. The research informants were selected using purposive sampling, consisting of individuals who were considered knowledgeable and directly involved in the issues under investigation, including the Production Coordinator, Maintenance Division, Laboratory Officer of Zone 1, Assistant Manager of Secretariat and Public Relations, and the Accounting and Budgeting Officer. Data were collected through interviews, observations, and documentation by applying data source triangulation to ensure data validity. The results indicate that the management of water production residues has been carried out in accordance with Standard Operating Procedures (SOPs); however, its effectiveness remains limited due to constraints in budget allocation, facilities, and waste treatment technology. In terms of environmental accounting implementation, the recognition, measurement, presentation, and disclosure of environmental costs have not been optimally integrated, as environmental costs are still recorded within general operational budgets without specific classification and detailed reporting. This condition reflects existing challenges in linking waste management practices with environmental accounting records. The main obstacles include limited technological capacity, insufficient human resources with expertise in environmental accounting, and the absence of specific regulations governing environmental cost recording. Therefore, clearer regulatory support, dedicated budget allocation, improved waste treatment technology, and employee training are required to ensure a more effective and sustainable implementation of environmental accounting.